2019
DOI: 10.1128/iai.00541-19
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia psittaci -Infected Dendritic Cells Communicate with NK Cells via Exosomes To Activate Antibacterial Immunity

Abstract: Dendritic cells (DCs) and natural killer (NK) cells are critically involved in the early response against various bacterial microbes. Functional activation of infected DCs and NK cell-mediated gamma interferon (IFN-γ) secretion essentially contribute to the protective immunity against Chlamydia. How DCs and NK cells cooperate during the antichlamydial response is not fully understood. Therefore, in the present study, we investigated the functional interplay between Chlamydia-infected DCs and NK cells. Our bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 96 publications
(111 reference statements)
1
24
0
Order By: Relevance
“…First, TNF-a works with IFN-g to inhibits the metabolism of host cells by increasing the activity of indoleamine 2, 3-dioxygenase (IDO), and restricts the growth of Chlamydia (36,56). Secondly, TNF-a influences the survival of Chlamydia in vivo by inducing apoptosis of host cells that provide suitable conditions for the growth of the organism (57)(58)(59). Furthermore, the adoptive transfer of TNF-a reduces the lung bacterial load of newborn mice infected with Chlamydia.…”
Section: Tnfmentioning
confidence: 99%
“…First, TNF-a works with IFN-g to inhibits the metabolism of host cells by increasing the activity of indoleamine 2, 3-dioxygenase (IDO), and restricts the growth of Chlamydia (36,56). Secondly, TNF-a influences the survival of Chlamydia in vivo by inducing apoptosis of host cells that provide suitable conditions for the growth of the organism (57)(58)(59). Furthermore, the adoptive transfer of TNF-a reduces the lung bacterial load of newborn mice infected with Chlamydia.…”
Section: Tnfmentioning
confidence: 99%
“…Through Toll-like receptor activation in response to pathogen-derived microbial products, DC and NK cells interact, resulting in NK activation and DC maturation [1]. In an in vitro model of Chlamydia psittaci infection, activation of NK cells and strong IFN-γ production may occur also by release of exosomes from infected DC [2].…”
Section: Introductionmentioning
confidence: 99%
“…Dutow et al elucidated the role of effector of the complement (C3a) in C. psittaci 02DC15 infection ( 22 ). Most recently, Radomski et al reported that C. psittaci 02DC15 infection of dendritic cells enhances exosome release, resulting in strong induction of IFN-γ production by natural killer cells and enhancement of apoptosis ( 24 ). Therefore, successful transformation using C. psittaci 02DC15 is particularly meaningful with respect to the biology of C. psittaci infection.…”
Section: Discussionmentioning
confidence: 99%
“…S8), we were able to show that all of the genes present in C. psittaci 6BC are encountered in C. psittaci 02DC15 as well, thus indicating their genetic equivalence. Due to the genome similarity between C. psittaci 6BC and C. psittaci 02DC15, C. psittaci 02DC15 is widely used for a number of immunological and cell biological studies, as well as animal infection trials (22)(23)(24)(25)(26)(27)(28). Reinhold et al established a bovine respiratory model of acute C. psittaci infection using strain 02DC15 (27).…”
Section: Figmentioning
confidence: 99%